Digital tools as promoters for person-centered care practices in chronic care? Healthcare professionals' experiences from rheumatology care - Emma Granström; Carolina Wannheden; Mats Brommels; Helena Hvitfeldt; Monica E. Nyström (BMC, 2020)
Abstract Background Person-centered care (PCC) emphasize the importance of supporting individuals' involvement in care provided and self-care. PCC has become more important in chronic care as the number of people living with chronic conditions is increasing due to the demographic changes. Digital tools have potential to support interaction between patients and healthcare providers, but empirical examples of how to achieve PCC in chronic care and the role of digital tools in this process is limited. The aim of this study was to investigate strategies to achieve PCC used by the healthcare professionals at an outpatient Rheumatology clinic (RC), the strategies' relation to digital tools, and the perceived impact of the strategies on healthcare professionals and patients. Methods A single case study design was used. The qualitative data consisted of 14 semi-structured interviews and staff meeting minutes, covering the time period 2017-2019. The data were analyzed using conventional content analysis, complemented with document analyses. Results Ten strategies on two levels to operationalize PCC, and three categories of perceived impact were identified. On the individual patient level strategies involved several digital tools focusing on flexible access to care, mutual information sharing and the distribution of initiatives, tasks, and responsibilities from provider to patients. On the unit level, strategies concerned involving patient representatives and individual patients in development of digital services and work practices. The roles of both professionals and patients were affected and the importance of behavioral and cultural change became clear. Conclusions By providing an empirical example from chronic care the study contributes to the knowledge on strategies for achieving PCC, how digital tools and work practices interact, and how they can affect healthcare staff, patients and the unit. A conclusion is that the use of the digital tools, spanning over different dimensions of engagement, facilitated the healthcare professionals' interaction with patients and the patients' involvement in their own care. Digital tools complemented, rather than replaced, care practices.